2010
DOI: 10.1017/s0016756810000737
|View full text |Cite
|
Sign up to set email alerts
|

A revised Aquitanian age for the emplacement of the Ronda peridotites (Betic Cordilleras, southern Spain)

Abstract: The hot emplacement of the Ronda peridotites (Betic Cordilleras) developed a dynamothermal aureole and partial melts that led to the intrusion of granite dykes in the peridotites. Previous geochronological data place rather broad limits for this event between 22 and 19 Ma. Analyses of neocrystalline zircon rims from large zircon populations yield a U-Pb SHRIMP age of 22.3 ± 0.7 Ma for the dynamothermal aureole formation, and intrusion ages of granite dykes between 22.6 ± 1.8 and 21.5 ± 3.8 support that conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 14 publications
(35 reference statements)
2
50
0
1
Order By: Relevance
“…Instead of the sequence described by Esteban et al (2008Esteban et al ( , 2011, Tubía et al (2013), and Platt et al (2013), tectonically located under the peridotites, we have found a magmatic formation and two metasedimentary formations in the same area, all located over the peridotites, in agreement with the previous description and cartography and Piles Mateos et al (1978a and b). These formations are described as follows.…”
Section: Geological Settingsupporting
confidence: 92%
See 2 more Smart Citations
“…Instead of the sequence described by Esteban et al (2008Esteban et al ( , 2011, Tubía et al (2013), and Platt et al (2013), tectonically located under the peridotites, we have found a magmatic formation and two metasedimentary formations in the same area, all located over the peridotites, in agreement with the previous description and cartography and Piles Mateos et al (1978a and b). These formations are described as follows.…”
Section: Geological Settingsupporting
confidence: 92%
“…This subject is one of the key points of the present article. Esteban et al (2008Esteban et al ( , 2011 and Tubía et al (2013) interpreted the Guadaiza unit as recording two "anatectic events", based on the assumption that this unit is tectonically thrust by the peridotites. The oldest events would originate the Istan migmatites, which has been dated as 319±8 Ma and 299±4 Ma.…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Thin zircon rims were also dated from a leucocratic gneiss of the Guadaiza unit right underneath the Ronda peridotites (locality Carratraca) and returned a range of U-Pb SHRIMP dates between 255 and 20 Ma (Platt and Whitehouse, 1999). Recently, Esteban et al (2011aEsteban et al ( , 2011b) dated zircons from mylonites of the Guadaiza unit, located at the contact and far from the contact with the Ronda peridotites (localitites Guadaiza and Yunquera, respectively), and metaquartzites layers within marbles and schists of the Ojén unit (locality Albornoque). They obtained U-Pb SHRIMP ages of ≈ 2700, ≈2200, ≈1200 and ≈650 Ma for the cores, and 20-43 Ma for the thin unzoned rims.…”
Section: Previous Geochronological Datamentioning
confidence: 99%
“…Partial melting in the crustal footwall has been associated with the hot crustal emplacement of the Ronda peridotites (Esteban et al, 2008;Torres-Roldán, 1983;Tubía et al, 1997Tubía et al, , 2013, whereas anatexis of the crustal rocks above the peridotite has been related to decompression melting during crustal thinning (Argles et al, 1999;Platt et al, 2003a). Numerous studies conducted in the area (or in equivalent units from the Rif in northern Morocco) have attributed the high-grade metamorphism and partial melting in these rocks, and in general in the crystalline basements of the BeticRif orogen, either to the Variscan (Acosta, 1998;Bouybaouène et al, 1998;Gómez-Pugnaire et al, 2004;Michard et al, 1997;Montel et al, 2000;Rossetti et al, 2010;Sánchez-Rodríguez, 1998) or the Alpine (Esteban et al, 2011a;Loomis, 1975;Rossetti et al, 2010;Sánchez-Rodríguez and Gebauer, 2000;Whitehouse and Platt, 2003) orogenies. This controversy obviously makes uncertain the P-T conditions reached during the Alpine orogeny, the geodynamic evolution of the entire Betic-Rif orogen, and even the age of the crustal emplacement of the Ronda peridotites.…”
Section: Introductionmentioning
confidence: 99%